Modified surgical procedure of corpus callosotomy: rostral corpus callosotomy via the transfrontal approach in dogs - Hasegawa, Daisuke; Asada, Rikako; Miura, Takayuki (Frontiers in Veterinary Science, 2025)
Corpus callosotomy (CC) is a surgical procedure for palliative epilepsy surgery targeting generalized seizures. In humans, total CC (TCC) is primarily performed in pediatric patients, whereas anterior CC is typically performed in adult patients to avoid postoperative disconnection (split-brain) syndrome, even though the antiseizure effect is inferior to TCC. In dogs, TCC may be more favorable; however, approaching and dividing the rostral part of the corpus callosum (genu) through a previously described bilateral rostrotentorial (dorsal) approach is challenging, particularly in meso- and dolichocephalic and/or large-breed dogs. This approach also risks damaging the rostral cerebral arteries that run along the rostral edge of the genu. Based on our experience, approaching and dividing the genu is easier, safer, and more reliable using the transfrontal approach. This report introduces the rostral CC (RCC) procedure via the transfrontal approach and presents three cases that underwent either transfrontal RCC combined with the dorsal approach to complete TCC or standalone RCC. Although the antiseizure efficacy of RCC alone remains unclear in dogs, this procedure may be useful for completing TCC.